Suicide Trends According to Age, Gender, and Marital Status in South Korea - Kim, Jung Woo; Jung, Hee Young; Won, Do Yeon; Noh, Jae Hyun; Shin, Yong Seok; Kang, Tae In (Omega: Journal of Death and Dying, 2019)
The purpose of this study is to examine suicide trends in South Korea, which has one of the highest suicide rates in the world. The results show that the male suicide rate outweighs that of females, the likelihood of committing suicide increases with age, and that, in regard to marital status, nonmarried people are the most at risk. In addition, several methods of reducing suicide rates are identified: the wider use of social networks to reduce social burden, the development of a social atmosphere where aging is accepted as a natural process, and the development of protection factors within families.